(3jGaJjI GdbOSs - (3hdjO GdCYXei(B.s; (3hdjO GdCYXei(B.s ((3LjRI (B:s (3eQcR GdCYdGe GdYQHi(B,s, 2006)
(3jJfGhd GdcJGH GdbVjI GdadSWjfjI ai TYQ hdjO GdCYXei GdPi jJfGhd bVGjG GdeSdejf (B.s
(3adSWjf (B- (3TYQ(B.s
Keywords: (3adSWjf (B- (3TYQ(B.s